Application of the meta-modelling method in Business Intelligence - Biniek, Zenon (Zastosowanie metody metamodelowania w Business Intelligence, 2020)
The article deals with the issue of conceptual modelling of the MOLAP database structures used in multidimensional data analysis for BI. Management information for decision-making purposes was collected in the MOLAP database and delivered to the user via the management cockpit. Building OLAP databases is discussed from the database designer point of view The meta model of the OLAP database was described in conceptual and logical terms. The work includes a critical analysis of the meta-model assumptions for the design of systems for multidimensional data analysis. A postulate to revise the classic meta-model was presented and a new type of relationship was proposed. The assumptions of the meta-model for modelling and simulating business decisions were presented, as well as the application of meta modeling to define business processes. Based on Gozinto graphs, the meta model of structural and technological developments was defined
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 4 (58), s. 50-66
Keywords: informatyka ekonomiczna